Reducing risk and accelerating delivery of a neutron source for fusion materials research - Surrey, E; Porton, M; Davenne, T; Findlay, D; Letchford, A; Thomason, J; Roberts, S; Marrow, T; Seryi, A; Connolly, B; Owen, H (Elsevier, 2014)
The materials engineering database relevant to fusion irradiation is poorly populated and it has long been recognized that a fusion spectrum neutron source will be required, the facility IFMIF being the present proposal. Re-evaluation of the regulatory approach for the EU proposed DEMO device shows that the purpose of the source can be changed from lifetime equivalent irradiation exposure to data generation at lower levels of exposure by adopting a defence in depth strategy and regular component surveillance. This reduces the specification of the source with respect to IFMIF allowing lower risk technology solutions to be considered. A description of such a source, the Facility for Fusion Neutron Irradiation Research, FAFNIR, is presented here along with project timescales and costs. © 2014 EURATOM/CCFE Fusion Association.